2002
DOI: 10.1038/sj.cgt.7700446
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-viral therapy of brain tumors by combination of viral therapy with cancer vaccination using a replication-conditional HSV

Abstract: Here we developed an effective therapeutic approach using a replication -conditional mutant of herpes simplex virus ( HSV ), G207, for the treatment of metastatic tumors in the immunologically privileged central nervous system. An experimental model of brain metastasis was developed using BALB / c mice that harbored both intracranial ( i.c. ) and subcutaneous ( s.c. ) mouse CT26 colon adenocarcinoma tumors. Intratumoral injections of G207 into s.c. tumors elicited cytotoxic T -cell responses not only to HSV bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…[22][23][24]28 Moreover, we demonstrated that the antitumor effect on distant, noninfected tumors involves tumor antigen-specific CTL responses induced by the intratumoral HSV inoculation. 23 Although several brain tumor antigens have been recently identified, [38][39][40] few glioma antigens recognized by glioma-specific CTLs have been isolated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24]28 Moreover, we demonstrated that the antitumor effect on distant, noninfected tumors involves tumor antigen-specific CTL responses induced by the intratumoral HSV inoculation. 23 Although several brain tumor antigens have been recently identified, [38][39][40] few glioma antigens recognized by glioma-specific CTLs have been isolated.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 For the induction of strong antitumor immune responses, we have used a replication-conditional HSV mutant, G207, to modify tumor cells directly in situ. [22][23][24][25][26] Using syngeneic tumor models with mouse CT26 colon adenocarcinoma cells, we have demonstrated that intratumoral inoculation with G207 elicits strong immune responses not only to the HSV but also to the tumor antigen. 23,24 Inoculation with G207 inhibits the growth of both the infected tumor and the noninfected contralateral tumor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…178,179 It appears that G207 inhibits tumor growth by two mechanisms: direct oncolysis via virus replication 166 and induction of tumor-specific immunity via an increase in cytotoxic T-cell (CTL) activity. 172,[180][181][182][183] Based on the promising preclinical data, G207 is now evaluated in clinical trials. Phase I clinical trials in patients with malignant glial tumors confirmed the safety of G207 virotherapy.…”
Section: Hsv-1 For Cancer Treatment Y Shen and J Nemunaitismentioning
confidence: 99%
“…43 This is in accordance with the observation that following intratumoral injection of so called oncolytic herpesvirus vectors for local tumor control, systemic antitumor activity with rejection of metastases at distant sites has been observed. 44 In this setting HSV vector-induced lysis of solid tumor cells is thought to initiate crosspriming events, [45][46][47] resulting in uptake of tumor-cell-derived proteins by professional antigen-presenting cells. 48 The observed expansion of activated T, NK and antigen-presenting cells in mice splenocytes supports a similar scenario underlying the antineoplastic effects induced by the replication-defective HSV-1 helper virus-dependent vectors.…”
Section: Hsv-1 Amplicons For Generation Of All Vaccinesmentioning
confidence: 99%